Do dental implants facilitate bone invasion in patients with oral squamous cell carcinoma? A case series. Issue 4 (April 2023) - Verstraeten, J.; Slootweg, P.J.; Cuijpers, V.M.; Meijer, G.J.
Abstract: Osseointegrated dental implants in the vicinity of oral squamous cell carcinoma (OSCC) will become more common given the increasing popularity of dental implants. Reports and studies of OSCC around dental implants are rare, as is the topic of how to handle OSCC surgically when implants are in contact with the tumour. In view of this uncertainty, a histological study was performed to assess tumour behaviour around implants. The aim was to determine whether an implant facilitates inward growth of the tumour and how this should be taken into account during staging and treatment planning. A total of 20 specimens were collected. The implants were macroscopically in contact with OSCC in 13 of the 20 specimens. Histologically, tumour tissue near the implant was indeed confirmed in nine of these cases. In seven cases, tumour invasion had led to resorption of the underlying jaw bone; tumour between the bone–implant interface was identified in only two of these cases, but without downward growth along the implant. In conclusion, no proof was found to confirm that the bone–implant interface is a preferred route for invasion. Therefore, dental implants in the vicinity of OSCC should not influence staging and treatment planning in this regard.